Travel and Tours Management System: Logistic II (Vendor Portal, Audit Management, Vehicle Reservation System, Fleet Management, Document Tracking System): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Travel and Tours Management System is an integrated and innovative system that processesrelated to travel and tours transactions, which are put together to form developing tours forcustomers, hiring new employees, logistics for the equipment to be used by the company,finances for the expenses that the company can use and administrative to serve as the mainhandle of the whole system. Logistic II is the management of the flow of products, information,and other resource transactions. This is the whole process for controlling the acquisition,storage, and distribution of resources.As a result, the researchers found three factors, which are PRODUCTIVITY, EFFICIENCY,and SECURITY. The implementation of the new and contemporary Travel and Tours LogisticII System, owned by Mblitz Travel and Tours, can provide more functionalities than before,including responsive web design, real-time tracking of deliveries, and more manageablecollaboration between vendors and contractors. The Travel and Tours Management SystemLogistic II will enhance visibility in the supply chain. This will enable the company to bettercontrol costs, tease out efficiencies, spot supply chain problems, and gain insights intoopportunities. It will also help to prevent loss in several ways. The company knows how manyitems it has on hand at any given time, can track movement and location so items won’t bemisplaced without notice, and ensures the storage and transport conditions that preventspoilage and damage. This project will use one of the most common network setups, which isthe star topology. It is designed with each node like workstations, printers, laptops, servers,etc. Connected directly to the central device called a network switch. It is used because startopology is reliable; if one cable or device fails, then all the others will still work. It is also high-performing as no data collisions can occur and less expensive because each device onlyneeds one I/O port.
Keywords: IT & Management